Challenges of E-Learning Effectiveness During the Covid-19 Pandemic in Historical Subjects - Mahadin, Mahadin; Rochalina, Corry Iriani; Ibrahim, Nurzengky (LPPM Undiksha, 2022)
Learning during the COVID-19 pandemic has become less effective because of a pandemic that requires students not to come to school. In addition, many parents complain about the fate of their children who never get a proper education. It also happens in historical subjects, where historical material taught in general must be delivered directly. This study aims to analyze the effectiveness of E-Learning learning during the pandemic in history learning. This type of research is a case study. The samples of this study were history teachers and students of class XI science. Data collection methods are interview, observation (observation), and study documentation. The sampling technique used is a purposive technique. The population of this study amounted to 143 students. Research instruments used as data collection tools such as interview guidelines and questionnaires. The data analysis technique used is qualitative analysis. The results of the study indicate that the planning and implementation of E-Learning learning as a solution to history subjects is in the excellent category because E-Learning learning can help the history learning process more broadly, for example, in the use of virtual museums and local museums. Cultural heritage tourism.